Early peak height velocity and cardiovascular disease mortality among Icelandic women. (December 2013) - Imai, Cindy Mari; Gunnarsdottir, Ingibjorg; Gudnason, Vilmundur; Aspelund, Thor; Birgisdottir, Bryndis Eva; Thorsdottir, Inga; Halldorsson, Thorhallur Ingi
Abstract Introduction. Early pubertal onset among girls has been associated with cardiovascular disease (CVD) risk factors. We examined whether timing of peak height velocity (PHV), an early marker of maturity, was associated with CVD mortality. Materials and methods. We analysed 973 Icelandic women, born 1921–1935, with annual childhood growth measures from ages 8–13 years, recruited into the longitudinal Reykjavik study 1968–1991. CVD deaths from recruitment to December 2009 were recorded. Results. Eighty-six women died from CVD, 42 deaths from coronary heart disease (CHD). Compared to girls with PHV after age 12, girls with PHV < 11 years and between 11 and 12 years had greater risk of CVD mortality, hazard ratio 1.87 (95% confidence interval 1.07–3.26, P = 0.028) and 2.56 (1.52–4.31, P < 0.001), respectively. Comparable associations were observed with CHD cases 2.27 (1.17–4.44, P = 0.016) as well as non-CHD CVD cases 2.21 (1.17–4.19, P = 0.015) when comparing girls with PHV after versus prior to age 12. Timing of PHV was not associated with traditional CVD risk factors in mid-life including body mass index and adverse lipid profiles or with all-cause mortality. Discussion. Earlier timing of PHV in girls may increase the lifetime risk of CVD mortality and may be an important determinant for later cardiovascular health.